Metastatic well-differentiated neuroendocrine tumor in the breast: A case report and literature review - Dongfang Yu; Yi Zhou (Elsevier, 2019)
Metastatic well-differentiated neuroendocrine tumors in the breast are rare and can be mistaken as invasive breast carcinoma due to their overlapping clinical, histological or radiological features. A 49-year-old female presented for evaluation of a left breast mass. Her past medical history was significant for an ileal well-differentiated neuroendocrine tumor with liver metastasis. Histology of breast biopsy shows nests of small uniform tumor cells with regularly dispersed chromatin. The tumor cells are positive for synaptophysin, chromogranin, CDX2, and ER (weak); and negative for CK7 and GATA3. These immunophenotypic features, in conjunction with the clinical history and cellular morphology, support the diagnosis of metastatic well-differentiated neuroendocrine tumor with ileal origin. Considering her asymptomatic breast lesion and indolent liver metastasis, she was offered close follow up and elective lumpectomy. This case reinforces the importance of recognizing a metastatic neuroendocrine tumor in the breast to ensure appropriate treatments.